Using Mobile Phone To Access Academic Result In Universiti Utara Malaysia - Ashraf Ali F., Abdul Jalil (2008)
This study was to find out the limitation of existing system in accessing student's results, find out new user requirements and measure the system usability. The respondents are all UUM students as they have experience in using the existing UUM application for checking academic result and they are also potential users of using this system. This study found that the system is acceptable and usable.